OBJECTIVE STRUCTURAL ANALYSIS OF THE NOVEL JARING KALAMANGGA BY SUPARTO BRATA - Rahman, Budiati; Prasetyo Aji, Sofi; Yuniarto, Sugeng (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2023)
The purpose of this research is to know the structural elements of the novel Jaring Kalamangga by Suparto Brata and the possibility of learning the novel Jaring Kalamangga by Suparto Brata at the high school level. The theory used is Nurgiyantoro’s structure theory. The object of the research is the novel Jaring Kalamangga by Suparto Brata. The research subject is focused on the objective structural analysis of literature (novel) and the possibility of learning it in high school. The data source of this research is the novel Jaring Kalamangga by Suparto Brata. The instrument of this research is the writer as an instrument assisted by literary books related to the object of this research and data recording paper. Data collection techniques used inductive data review techniques. Data analysis techniques used formal method techniques, namely analysis with or considering formal aspects, aspects of form, namely elements of literary works. The technique of presenting the results of the analysis used informal techniques. The results showed that the novel Jaring Kalamangga with the theme of persistence in seeking the truth can encourage the exposure of crime. In other words, a serious effort will succeed. The elements of the story include: theme, character and characterization, plot, and setting. The plot used is a straight plot; the characters in the novel Jaring Kalamangga are Handaka, Pak Sanggar Padmanaba, Pitrin, Tuan Adib Darwan, Tinuk, Tranggana, Tuan Muin Jingga, Mbok Gin, Inspector Cahyadiwangga, Doctor Azis, Tashudin; and these characters have different characters. The settings used include: place setting, time setting, atmosphere setting, and social setting. The novel Jaring Kalamangga by Suparto Brata can provide good moral messages for humans through the characters in the story. The novel Jaring Kalamangga presents persistence in finding the truth of a matter, all good and bad human actions will get their reward. Learning the novel Jaring Kalamangga by Suparto Brata fosters a brave attitude to do good and enthusiasm.